Effects Of Contractors’ Delay Factors On Building Project Performance Among Kuantan Malaysian Construction Industry - N.S.A, Samsudin; Adeleke, A. Q.; Ajibike, W. A. (International Society for Everant Publisher, 2020)
In Malaysia, construction companies have played a great role in the growth of the country’s economy over the years. Timely completion of construction projects is a major criterion of project success. Failure to complete the project on time will ultimately result in a delay. The need to control the causes of delays during the construction process arise when the number of delay project has been increased from time to time. Hence, it is essential to identify the causes of this problem from the early stage of the construction project. Some studies in the construction field have shown that quality performance by contractors has been decreasing and affecting the organization’s level of advancement in the industry. To address the issue, this paper aims to investigate the significant relationship between contractor experience and building project performance in Kuantan Malaysian construction projects, and to examine the significant relationship between effective communication and building project performance in Kuantan Malaysian construction projects. Eighty-nine (89) construction companies that registered under the CIDB Malaysia among Kuantan, Malaysia construction companies were surveyed. PLS-SEM technique was used in this research to assess both the measurement and structural models. The results showed that contractor experience and effective communication played a significant positive relationship on building project performance among construction companies operating in Kuantan, Pahang, Malaysia.